ANALISIS KUASA PADA PRAKTIK KELEMBAGAAN PA’TOTIBOYONGAN DI MAMASA - Risma Junita (Jurnal Sosiologi Reflektif, 2016)
This paper elaborates the issue of agricultural resources management processes based on local institution called pa’totiboyongan in the Village of Ballatumuka, Mamasa. This research employs a power analysis framework to analyze the management processes in distributing agricultural resources. In a practical level, the agricultural resource management processes have involved various actors who have different roles and interests. These different roles and interests reveal the patterns of power relations among the actors in forms of conflct, resistance, persuasion, and collaboration. Furthermore, the inflence of power relations among the actors on preserving the existence of pa’totiboyongan is clearly apparent. The result shows that the agricultural resources management processes are based on three important aspects: economics, ecological, and social-culture of  society.